2011
DOI: 10.1007/s12306-011-0120-0
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of the mayo clinic congruent radial head plate: cadaveric study

Abstract: In the last few years, several anatomical plates have been introduced to improve the results of ORIF in Mason Type II and III radial head fractures. However, no study analyzed whether currently used plates match adequately the profile of the proximal radius in the "safe zone". In the present investigation, we evaluate the congruence between the proximal radius and a currently used plate. Forty-four radial dried cadaveric bones were analyzed. The plate congruence was evaluated qualitatively and quantitatively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…These investigations showed that none of the tested plates exhibited good congruence to the safe zone in most cases analyzed, nor was a significant improvement found in the plate-bone congruence after plate bending. 12,13 In keeping with this, our results suggest that if the different morphological types of the proximal radius are not taken into account by the plate design, an osteosynthesis of the radial head may fail to reconstitute the original morphology, especially when the severity of injury causes a loss of anatomical landmarks. We found that in the presence of a type A radius, the positioning of a pre- 17,20 -22 we believe that preoperative templating of the contralateral radius may be useful before operating on comminuted Mason type II and III fractures.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…These investigations showed that none of the tested plates exhibited good congruence to the safe zone in most cases analyzed, nor was a significant improvement found in the plate-bone congruence after plate bending. 12,13 In keeping with this, our results suggest that if the different morphological types of the proximal radius are not taken into account by the plate design, an osteosynthesis of the radial head may fail to reconstitute the original morphology, especially when the severity of injury causes a loss of anatomical landmarks. We found that in the presence of a type A radius, the positioning of a pre- 17,20 -22 we believe that preoperative templating of the contralateral radius may be useful before operating on comminuted Mason type II and III fractures.…”
Section: Discussionsupporting
confidence: 67%
“…12 Briefly, we positioned a currently available plate (Mayo Clinic Congruent Radial Head Plate; AcuMed, Hillsboro, OR) in the center of the safe zone according to standard surgical technique. In cases showing a mismatch between plate and bone, the implant was positioned adherent to the radial head circumference.…”
Section: Relationship Between Safe Zone Morphology and Plate Congruencementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, qualitative evaluation was used in some studies. In their studies, Giannicola et al [22,23] evaluated the congruency between an anatomic plate and proximal radius on cadaveric bones by two independent observers and congruence was classified as good, moderate or poor. In this study, the volume of free space between the plate and bone was used as a criteria.…”
Section: Discussionmentioning
confidence: 99%